Expanding the Molecular-genetic Spectrum of Canalicular Adenoma-like Subtype of Pleomorphic Adenoma of Salivary Glands - Klubíčková, Natálie; Loghides, Frederica; van den Hout, Mari F.C.M.; Costes-Martineau, Valérie; Ferrara, Gerardo; Rito, Miguel; Hájková, Veronika; Grossmann, Petr; Šteiner, Petr; Kovářová, Inka; Michal, Michal; Leivo, Ilmo; et al. (Lippincott, Williams & Wilkins, 2025)
Canalicular tumors of the salivary glands have recently emerged as an entity characterized by distinct morphology and recurrent HMGA2 gene rearrangement. In this study, we analyzed 40 cases intending to elucidate their features further. The monophasic or biphasic tumors exhibited a growth pattern of interconnected anastomosing trabeculae and canaliculi, accompanied by a classical pleomorphic adenoma in one-third of the cases. Invasive growth into surrounding adipose tissue was revealed in one case which was, therefore, diagnosed as epithelial-myoepithelial carcinoma. Although the tumor cells uniformly expressed HMGA2 protein in all cases, cytokeratin 7, S100 protein, and SOX10 displayed either diffuse positivity or highlighted the luminal and abluminal cell populations, respectively. Areas with morphological oncocytoid change and AR-immunopositivity of luminal cells were seen in 13/14 (93%) of tested biphasic cases. HMGA2 rearrangement was detected by RNA-sequencing in 30 cases. The most common alteration was an HMGA1::WIF1 fusion, but several novel or rare fusion partners were identified, including ARID2, FHIT, MSRB3 and its antisense variant MSRB3-AS1, IFNG-AS1, and the long intergenic region LINC02389. In addition, FISH revealed HGMA2 break-apart in the remaining 10 cases where targeted sequencing failed to detect any alteration or where RNA sequencing could not be performed. Notably, the loss of the 3'-untranslated region of HMGA2 emerges as the common denominator for the described rearrangements, possibly disrupting its negative regulation by small regulatory RNAs. Awareness of this lesion ensures appropriate diagnosis and clinical management, especially with regard to the possibility of malignant transformation described in this and previous studies.